'The Tower and the Quest': A storytelling space for avatars. Issue 1 (1st March 2013) - Ayiter, Elif; Dahslveen, Heidi
In this article, we discuss a project that was co-authored by a storyteller and a visual artist in the metaverse of Second Life in 2009. The aim of the project was to create a storytelling space that would be used by its visitors to create their own unique narratives, as well as their own original performances, all of which would take their trajectories by being immersed in a virtual architecture/landscape, through avatar costumes and a substantial library of dramatic poses and animations that were put at their disposal by the authors at the location of the event. The project wove together several concepts: these are Roy Ascott's tenets of 'distributed authorship' and 'participatory poesis', which were brought together with a term that was coined by Axel Bruns to describe novel collaborative electronic forms of creative output in which the roles of the 'user' and the 'producer' have become merged, manifesting as a novel type of online behaviour that the author defines as 'Produsage'. These primary concepts were substantiated by research that combined the fields of performance art, storytelling, memory arts and the usage of mnemonic devices, including the Renaissance notion of the 'memory theatre' with Cyberpsychology, particularly in relation to avatar studies.